PENERAPAN MODEL PEMBELAJARAN LEARNING CYCLE UNTUK MENINGKATKAN HASIL BELAJAR IPA SISWA KELAS V SD NEGERI 105 PEKANBARU - Nia Kurniawati; Mahmud Alpusari; Hendri Marhadi (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract: This research was conducted because of the result of learning science study grade V SD Negeri 105 Pekanbaru. KKM achieved by school was 70. From 41 students who achieve KKM just 17 students (41.46%) while students who did not achieve KKM is 24 students (58.53%) with a grade average of 61.82. The purpose of this research to improve learning outcomes IPA class V SD Negeri 105 Pekanbaru with the application of learning models Learning Cycle. The results obtained by the average value of 61.82 basic score increased in the first cycle of 18,14% to 7304. In the second cycle the average value of students also increased by 29,79% to 80.82. On the basic of classical completeness score IPA student learning outcomes is only 41,46% (not finished). After the process of application learning model Learning Cycle in the first cycle classical completeness increased to 73,17% (not finished), and the second cycle of classical completeness obtained are increased to increase to 87,80% (finished). Activities of teachers at the first meeting of first cycle acquire a percentage of 65% with enough categories. The second meeting increased to 75% in enough categories. In the first meeting of second cycle increased to 80% with good category. At the second meeting increased to 85% with good category and at the third meeting increased to 90% with very good category. Activities of students in the first meeting of the first cycle acquire a percentage of 60% with enough categories. The second meeting increased to 65% in enough categories. In the first meeting of the second cycle increased to 75% with good category. At the second meeting increased to 85% with good category and at the third meeting increased to 90% with very good category. This the implementation of learning cycle model can improve student learning outcomes IPA.Keywords: Learning Cycle, Learning Outcomes IPA